MATEMATICAL MODELLING FOR PRODUCTIVITY OF PURPLE SWEET POTATO (IPOMEA BATATAS) CULTIVATED BY APPLICATION OF LIQUID ORGANIC FERTILIZER FROM MARMOT (CAVIA PORCELLUS) WASTE - Nur Fatimah, Anisah
Purple sweet potato (Ipomea batatas) is a local plant that classified as a functional food commodity. Fertilizing is done to improve soil condition and provide nutrient needed by plants. Liquid organic fertilizer (LOF) from guinea pig (Cavia porcellus) waste decomposition has the potential to support purple sweet potato productivity due to the high content of potassium. Mathematical modeling is needed to help practioners in decision making and planning of large-scale agriculture production. This study aims to quantify the purple sweet potato's plant growth parameters cultivated according to the BALITKABI procedure with the application of LOF from guinea pig and determine mathematical models of plants productivity. Cultivation with the application of LOF from guinea pig waste resulted in stover productivity of 27.06 tons/ha and fresh tubers of 22.56 tons/ha. The harvested tubers have a high uniformity (grade A) and first-class quality according to SNI. Through Goodness of Fit analysis, the Gompertz model is the best model to represent the purple sweet potato’s productivity during all stages of development. The equation for the fresh weight productivity of shoots, roots, and tubers are ????=1064 ????(?2.702????^104? ?????0.1????)), ????=19.45 ????(?4.761????+08? ?????0.4????)), and ????=282 ????(?100? ?????0.1????)). The equation for dry weight productivity of shoots, roots, and tubers are ????=128.4 ????(?228.5? ?????0.1????)), ????=5.339 ????(?106.6? ?????0.1????)), and ????=430 ????(?1.6?104? ?????0.1????)). From the equations, it can be inferred that the optimum harvesting time based on the optimum fresh weight are on the 15th to 19th weeks after planting. However shorter planting period might result in different tuber composition that need to be evaluated in the future.